Retail Macro-location Factors: Empirical Evidence from the Portuguese Shopping Centres - José Cadima Ribeiro; José Freitas Santos (European Regional Science Association (ERSA), 2003)
Shopping Centres have appeared in Portugal in the beginning of the seventies and have consolidated their presence from the eighties onwards. This study aims to identify the retail macro-location factors that attracts or deters the location of shopping centres at regional (municipality) level. Using OLS regression, we tested some hypothesis as pointed out by the theory, namely the number of potential consumers, their purchasing power, the presence of competitiors, accessibility to the shopping centre and costs (e.g., land, installation). The results allow for the acceptance of the hypothesis which unveil that the promoters of shopping centres seems to value highly the size of the market, both in terms of potential consumers and purchasing power. On the other hand, due to lack of atatistical significance, we cannot infer about the other hypothesis formulated above.
Keywords: 330